PENGARUH KUALITAS JASA AUDITOR INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN INTERN PADA HOTEL BERBINTANG EMPAT DAN LIMA DI BALI - YADNYANA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009))
This research aims to obtain empirical evidences about the impact of internal auditor service quality on internal control effectiveness in four- and fivestar hotels in Bali. Sample consists of 56 hotels and determined using stratified random sampling method. Respondents are staffs in accounting and internal audit sections. Data are analyzed using multiple linear regressions. Simultaneous test result shows R2 = 0,327; meaning that all variables of internal auditor service quality affect the effectiveness of internal control for 32,7 percent, while 67,3 percent are influenced by other variables not included in this research. The meaningful level of the influence of independent variables simultaneously on internal control effectiveness is found by conducting F-test with result: Fcount = 4,863 which is larger than Ftable (0,05, 56) = 2,37, meaning that internal auditor service quality affect internal control effectiveness significantly. Result of partial test shows p-values as follows: independence variable: 0,385; professional judgment: 0,212; scope of audit: 0,004; audit work: 0,121 and management of internal audit section: 0,557. The only significant variable is scope of audit.
Keywords: internal auditor service quality, accounting information quality, professional judgment, audit work, internal audit, and internal control effectiveness